COVID-19 In General - Muhammad Subkhan (Universitas Muhammadiyah Surabaya, 2020)
Abstract The first time China reported a mysterious pneumonia that occurred on December 31, 2019 with an unknown cause, Coronavirus is an RNA virus strain, of the Coronaviridae family. Most Coronaviruses infect animals and circulate in animals. The incubation period for SARS-CoV- 2 ranges from 1 to 14 days. Presymptomatic or asymptomatic transmission during the incubation period plays an important role in the control of the COVID-19 pandemic. Worsening of clinical conditions occurs approximately 7 to 14 days after onset. It is known that COVID-19 infection in the lungs consists of three phases, namely: 1. The initial stage of inoculation and the beginning of disease formation; 2. The formation of lung disease, viral replication and local inflammation in the lungs; 3. This phase occurs when the inflammatory response of the host increases, even when the viral load begins to decrease, there is some organ damage where the lung is the main target organ of COVID-19, accompanied by several organ injuries as follows:: gallbladder, kidneys, and other organs. The criteria for the severity of COVID-19 consist of: asymptomatic or presymptomatic, mild, moderate, severe, and critical. Radiological images play an important role in diagnosis and provide guidance for treatment, the sensitivity of chest CT scans is greater than real-time polymerase chain reaction (RT-PCR) for diagnosis of COVID-19, and chest CT scans can be used to screen COVID-19 in patients. with symptoms but negative RT-PCR.Keyword: Covid-19, RNA virus, Infection in the lung, Severity of covid-19